2022
DOI: 10.5483/bmbrep.2022-0183
|View full text |Cite
|
Sign up to set email alerts
|

Aging of hair follicle stem cells and their niches

Abstract: Hair follicles in the skin undergo cyclic rounds of regeneration, degeneration, and rest throughout life. Stem cells residing in hair follicles play a pivotal role in maintaining tissue homeostasis and hair growth cycles. Research on hair follicle aging and age-related hair loss has demonstrated that a decline in hair follicle stem cell (HFSC) activity with aging can decrease the regeneration capacity of hair follicles. This review summarizes our understanding of how age-associated HFSC intrinsic and extrinsic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 101 publications
0
8
0
Order By: Relevance
“…Details about the different factors contributing to this have been reviewed recently. 41 In humans, it is well known that genetic risk factors contribute to the development of androgenic alopecia. 14,33 A well-known example for the adaptation of the hair coat to environmental factors is the seasonal changes of the hair coat.…”
Section: Systemic and Environmental Influences On The Hcmentioning
confidence: 99%
See 2 more Smart Citations
“…Details about the different factors contributing to this have been reviewed recently. 41 In humans, it is well known that genetic risk factors contribute to the development of androgenic alopecia. 14,33 A well-known example for the adaptation of the hair coat to environmental factors is the seasonal changes of the hair coat.…”
Section: Systemic and Environmental Influences On The Hcmentioning
confidence: 99%
“…looking at skin biopsies from dogs and horses are in agreement that the anagen peaks in autumn and spring and a higher percentage of telogen follicles is seen in summer and winter. 4,5,13,41,55,75,76,79,80…”
Section: The Hcmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, a new group of aging studies has also shown that aging can be associated with stem cell exhaustion. NIH researchers have shown that with aging, stem cells lose adhesions and start moving away from base of the follicle [ 31 , 32 ]. These studies were part of the overall aging process studies, and hair follicles were a good model for these studies.…”
Section: Reviewmentioning
confidence: 99%
“…But how exactly does it cause hair follicle regeneration? In fact, telomere shortening impairs the mobilization and proliferation of HFSCs, exhibiting a follicle aging phenotype of thinner hair, hair loss, or gray hair, 28 which may be due to the corresponding negative effects on DPCs and HF melanocytes. Overexpression of TERT or reintroduction of telomerase can reverse this defect, activate quiescent HFSCs and melanocyte stem cells, fight HF aging, and facilitate HF regeneration 29 …”
Section: Telomerase Activation Positively Promotes Hair Growthmentioning
confidence: 99%